FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA UMKM (Studi pada UMKM Depot Air Galon di Kecamatan Tampan Kota Pekanbaru) - Ningrum Kusuma Sekar; Nuryanti Nuryanti; Pramadewi Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of this study was to examine the effect of capital, ability, andexperience on the performance of Air Gallon SMEs in Pekanbaru City. Thepopulation in this study is the Water Gallon MSME in Pekanbaru City in 2022,amounting to 657 MSMEs. With the Slovin formula, the number of respondents(samples) in this study was 87. In this study, the sampling technique used waspurposive sampling technique. The types of data used in this study are primarydata and secondary data. The data collection technique used in this study is aquestionnaire (Questionnaire). Data analysis used multiple linear regression. Theresults showed that capital, ability, and experience partially and simultaneouslyhad a positive and significant effect on the performance of MSMEs. Keywords: MSME Performance, Capital, Ability, Experience